Effects of High-Rate Frequency Modulation Treatment on Malondialdehyde in Diabetic Polyneuropathy - KAVAK*, S.; DULGER†, H.; TULGAR‡, M.; ALKIS§, I. (Asian Journal of Chemistry, 2009)
This study is planned to investigate the effects of transcutaneouselectrical nerve stimulation (TENS) treatment on patients which havediabetic polyneuropathy. Fourteen diabetic polyneuropathy patients sufferingischemic pain were examined during the cure. Malondialdehyde (MDA)and glycemia levels were determined by collecting 5 mL blood samplesfrom 14 patients 24 h before beginning the treatment. In case 50 Hzsignals as high-rate frequency modulation (HRFM; continuous pulseschanged from 90 Hz to 55 Hz over 90 msec, 1.3 times a second), wereapplied to patients as long as 20 d for 20 min a day. Transcutaneouselectrical nerve stimulation (TENS) treatment increased significantlyfree oxygen radicals (p < 0.05). The levels of MDA before TENS werecompared to the levels of MDA after TENS and the end of the followingterm of 20 days by paired sample test and a meaningful increase wasseen significantly (p < 0.01). Besides, glycemia levels were decreasedsignificantly before TENS-after TENS treatment (p < 0.01) and notchanged before TENS and the end of the following term of 20 d (p > 0.05).Moreover, it was observed that MDA levels were decreased significantlybetween in the final of the treatment and the end of the followingterm of 20 d (p < 0.01). Glycemia levels were not changed significantlyafter TENS and the end of the following term of 20 d (p > 0.05). Accordingto this results, it is observed that TENS treatment has been positiveeffect on polyneuropathy.